Geneva Launch of IFPRI's 2016 Global Food Policy Report - Fan, Shenggen (2016)
Presented by IFPRI Director General Shenggen Fan in Geneva, Switzerland, on April 12, 2016. More info: https://www.ifpri.org/event/geneva-launch-ifpris-2016-global-food-policy-report